Role of RFID on Store Operational Performances – A Prospect of Inventory Management Practice - Jena, Duryodhan; Panigrahi, Rashmi Ranjan; Gangwar, Veer P.; Bhuyan, Anil Kumar (International Journal of Psychosocial Rehabilitation, 2020)
RFID is emerging tool used for tracking, identifying stocks, physical object. In competitive business world technologies play vital role towards bringing operational efficiency business unit. In this paper an attempt has been made to know the efficient RFID practices for improving operational performance of selected retails stores in India. Empirical relationship cab measured through Different statistical tools i.e. Correlation, regression and factor analysis., data have been collected from key officials of retail units i.e. Store manager, operations manager, purchase manager, etc. The study concludes that RFID is most efficient practices and it has significant impact on operational performance of retail store and also contribute to the existing body of knowledge as well as helping the management practitioners of retail Industry.